Potassium supplying capacity and contribution of non-exchangeable potassium in wetland rice soils in Bangladesh - Saiful Islam; Gathala, Mahesh K.; Timsina, Jagadish; Dutta, Sudarshan; Muhammad Salim; Majumdar, Kaushik (Informa UK Limited, 2023)
Information on soil potassium (K) supplying capacity, K-depletion, and contribution of exchangeable and non-exchangeable K in wetland rice ecology is limited. Understanding of K dynamics of different soil types can be a guideline for better K-fertilizer management and sustainable soil K use to achieve sustainable rice yields. To understand this soil K-supplying capacity to rice plants, a pot study with two K levels (K0 and K100 mg K kg-1 soil) was conducted with seven successive rice crops grown up to the panicle initiation stage using 18 different soils collected from across Bangladesh. The cumulative soil K-supplying capacity (242–758 mg K kg-1 soil) varied significantly (P ≤.001) among soils, showing a strong positive relationship (R2 = 0.78) with NH4OAc K. The potential K-supplying capacity of these soils was the highest (758 mg K kg-1 soil) in Mithapukur (AEZ 3-Tista Meander Floodplain) and the lowest (242 mg K kg-1 soil) in Barura (AEZ 19-Old Meghna Estuarine Floodplain). In K0 soils, the successive cycles of rice resulted in continuous depletion of both non-exchangeable and exchangeable K pools. The concentration of both exchangeable and non-exchangeable K was maintained and almost balanced in K100 soils compared to K0 with successive rice cropping. Non-exchangeable K contribution to K nutrition of rice plants during the seventh cropping ranged, respectively, from 83% to 93% and 26% to 55% in K0 and K100 soils. Results reveal the importance of a non-exchangeable K pool in K-supplying to plants in wetland rice production systems with different soil types.